2008
DOI: 10.1016/j.cam.2007.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of time fractional reaction–diffusion systems

Abstract: We study a fractional reaction-diffusion system with two types of variables: activator and inhibitor. The interactions between components are modeled by cubical nonlinearity. Linearization of the system around the homogeneous state provides information about the stability of the solutions which is quite different from linear stability analysis of the regular system with integer derivatives. It is shown that by combining the fractional derivatives index with the ratio of characteristic times, it is possible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(106 citation statements)
references
References 28 publications
0
101
0
Order By: Relevance
“…It has been found that in the case of the Seki-Lindenberg model, (2.1), the oscillatory mode of a short-wave instability disappears. Note, that a short-wave oscillatory instability has been revealed for that model outside the region of its physical relevance for subdiffusion-limited reactions, when γ > γ 0 > 1 [51], [53], [57], [58].…”
Section: Instabilities and Pattern Formationmentioning
confidence: 78%
“…It has been found that in the case of the Seki-Lindenberg model, (2.1), the oscillatory mode of a short-wave instability disappears. Note, that a short-wave oscillatory instability has been revealed for that model outside the region of its physical relevance for subdiffusion-limited reactions, when γ > γ 0 > 1 [51], [53], [57], [58].…”
Section: Instabilities and Pattern Formationmentioning
confidence: 78%
“…In the last few decades, differential equations with derivatives of non-integer order attract the attention of the researchers as such equations provide a very suitable tool for description of many important phenomena in physics, geophysics, chemistry, biology, engineering and solid mechanics (see, for example, Gafiychuk et al 2008;Herrmann 2011;Magin 2006;Mainardi 2010;Povstenko 2015a;Sabatier et al 2007;Tarasov 2010;Tenreiro Machado 2011;Uchaikin 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While this does exclude certain applications, many interesting and relevant models can still be considered such as fractional phase-field models [12,14,15] or the fractional FokkerPlanck equation [48]. They also appear in many applications such as the anomalous diffusion [52], pattern formation using fractional derivatives [28], and also the simulation of fractional phase-field equations such as the Allen-Cahn equation [15]. Additionally, the low-rank approximation presented in this paper also applies in the case where the spatial domain is more complicated.…”
Section: Model Problemsmentioning
confidence: 99%